Utilização de creme de papaína e extrato liofilizado das raízes de salsa (Petroselinum crispum) contra Escherichia coli multirresistente em abscesso em equino - Orlandini, Carla Faria; Boscarato, André Giarola; Moura, Rodrigo Assunção; Sapateiro, Patrícia; Gazim, Zilda Cristiani; Lourenço, Emerson Luiz Bothelho; Alberton, Luiz Romulo (Acta Scientiae Veterinariae, 2017)
Background: Due to the bacterial resistance to conventional antibiotics, studies on natural products with antibacterial or bactericidal activity are becoming more and more frequent. Among multi-resistant bacteria, Escherichia coli is a producer of extended-spectrum beta-lactamase (ESBL). Papain, coming from papaya latex (Carica papaya), stands out for its capacity to degrade the devitalized tissue that delays the healing process. Parsley (Petroselinum crispum) has been studied, mainly for its diuretic, antioxidant and antimicrobial properties. The aim of this work was to report the use of these two phytotherapic agents in an equine presenting abscess infected by multi-resistant ESBL producing E. coli. Case: A four and a half year old male neutered equine weighing 400 kg of undefined race (SRD) was admitted to the Veterinary Hospital of the Paranaense University (UNIPAR), presenting an increased volume on the left side of the middle third of the neck, one year ago, probably due to an intramuscular injection in the splenius muscle performed by the animal’s owner, who did not remember which drug had been applied. Physical examination revealed a characteristic abscess lesion that involved the subcutaneous and muscular tissue of approximately 10 cm in diameter, and presented a fistulous trajectory with purulent content drainage and pain upon palpation. The animal was initially submitted to surgical drainage of the abscess and to systemic treatment with ceftiofur. In view of the failure of the therapy proposed, the lesion was treated with 2% papain cream and, subsequently, in association with lyophilized parsley extract (Petroselinum crispum) after the identification of the presence of multi-resistant ESBL producing E. coli, isolated from the lesion and identified through standard laboratory tests. The use of 2% papain cream reduced the inflammatory process and fibrous tissue. Lyophilized parsley root extract was effective against infection by multi-resistant bacteria. Discussion: The reduction of purulent secretion and the size of the inflammatory process are due to the proteolytic activity of papain, which decreases bacterial adhesion, and the degree of wound contamination, promoting healing. Several studies have indicated the bacteriostatic and bactericidal activity of papain, but in some trials, this effect was only found in a concentration of 10% for Pseudomonas aeruginosa and Staphylococcus aureus, and no effect for E. coli bacteria. In vitro studies have shown that the essential oil of Petroselinum crispum leaves and stems is more effective than the essential oil of seeds against this bacterium. Reports of isolation and bacterial identification of wounds and abscesses of horses present a large amount of microorganisms, but the presence of multi-resistant E. coli is uncommon. In other countries, the presence of this bacterium in wounds and other regions has been described in this species. In the Netherlands and Germany, the presence of ESBL producing E. coli in horses was detected in clinical samples of pus, stomach, uterus, feces and synovial fluid, presenting a real risk of human contamination by these resistant bacteria. In this sense, the study of antimicrobial agents has great scope, being a crucial point in several sectors of the pharmaceutical field. The phytotherapeutic association, used in this case, represents a possible promising, low-cost alternative for the treatment of contaminated wounds, emphasizing the importance of studies involving alternative treatments for bacterial resistance.